HUBUNGAN TEKANAN DARAH INTRADIALISIS DENGAN KEJADIAN FATIGUE PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI KLINIK PANDAONI MEDIKA JAKARTA - Talita Alifa Salsabila (2023)
Hemodialysis patients often experience a decrease or increase in intradialysis blood pressure. Hemodialysis therapy certainly has great benefits for patients, but there are negative impacts or complications from this therapy, namely physical complaints such as fatigue. The purpose of this study was to analyze the relationship between intradialysis blood pressure and the incidence of fatigue in patients with chronic renal failure undergoing hemodialysis at Pandaoni Medika Clinic Jakarta. This quantitative study used a cross sectional method with a correlational design. The sampling technique was purposive sampling method and the total sample that met the inclusion and exclusion criteria was 82 respondents. Data were collected using observation sheets and FACIT questionnaires. The results obtained an average age of 54 years with the majority of male gender (51.2%). The last education of the respondents was mostly high school (40.2%) and the majority did not have a job (41.5%). Hypertension was the most common disease suffered by respondents (43.9%). The average length of hemodialysis was 36 months with an average IDWG of 4.3%. Pearson correlation test showed that there was no relationship between intradialysis blood pressure from the first hour to the fifth hour and the incidence of fatigue (p-value > 0.05).